2018
DOI: 10.1021/acs.langmuir.7b04045
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal Spreading Dynamics of Self-Rewetting Droplets

Abstract: We experimentally studied the spreading dynamics of binary alcohol mixtures (and pure liquids for reference) deposited on a heated substrate in a partially wetting situation under nonisothermal conditions. We show that the spreading mechanism of an evaporating droplet exhibits a power-law growth with early-stage exponents that depend strongly and nonmonotonically on the substrate temperature. Moreover, we investigated the temporal and spatial thermal dynamics in the droplet using infrared thermography, reveali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Mamalis et al. (2018) also saw an increase in the spreading exponents with substrate temperature in their experiments with self-rewetting droplets. Additionally, when the temperature is increased, the number of fingers produced at the contact line (see figure 7 and § 4.3 for a detailed discussion of this instability) also increases, with approximately 18 seen at C, 20 at C and 21–24 seen at C.…”
Section: Experimental Findingsmentioning
confidence: 83%
See 2 more Smart Citations
“…Mamalis et al. (2018) also saw an increase in the spreading exponents with substrate temperature in their experiments with self-rewetting droplets. Additionally, when the temperature is increased, the number of fingers produced at the contact line (see figure 7 and § 4.3 for a detailed discussion of this instability) also increases, with approximately 18 seen at C, 20 at C and 21–24 seen at C.…”
Section: Experimental Findingsmentioning
confidence: 83%
“…This is likely due to the more rapid development of a concentration gradient when the droplet touches the substrate as ethanol evaporates more vigorously at the higher temperatures. Mamalis et al (2018) also saw an increase in the spreading exponents with substrate temperature in their experiments with self-rewetting droplets. Additionally, when the temperature is increased, the number of fingers produced at the contact line (see figure 7 and § 4.3 for a detailed discussion of this instability) also increases, with approximately 18 seen at T w = 30 • C, 20 at T w = 50 • C and 21-24 seen at T w = 70 • C. The finger length, which we define as the distance from the apparent contact line of the bulk droplet to the apex of the extended finger, also increases with substrate temperature as a higher evaporation rate drives the instability.…”
Section: Variation In Temperaturementioning
confidence: 90%
See 1 more Smart Citation
“…As we investigate the thermo-capillary driven flow of a millimetre size bubble, one can also easily achieve the value of Reynolds number (Re = 10) and the range of the Weber number considered in the present study. Recently, Mamalis et al [36] have measured the surface tension of solutions of water + 1-butanol 5 % volume and water + 1-pentanol 2 % volume and showed that surface tensions of these fluids exhibit parabolic dependencies with temperature (see Figure 4 of Ref. [36]).…”
Section: Resultsmentioning
confidence: 99%
“…These studies show that the behaviour of a bubble or droplet in or of a self-rewetting fluid can be qualitatively different from that for an ordinary fluid. Specifically, the theoretical studies by Karapetsas et al [35] of the motion of a droplet on a heated substrate, and by Tripathi et al [36] of the rise of a bubble in a vertical channel, as well as the experimental studies by Shanahan and Sefiane [37] of the motion of a bubble in a mean flow, by Mamalis, Koutsos and Sefiane [38] of the motion of a droplet on a heated inclined substrate, by Mamalis, Koutsos and Sefiane [39] of the rise of a bubble in a vertical micro-channel, and by Mamalis, Koutsos and Sefiane [40] of the spreading of a droplet on a heated substrate, all demonstrate this. In the present work we seek to bring further insight into this problem by formulating and analysing a theoretical model for the unsteady motion of a long bubble or droplet in a self-rewetting system in a non-uniformly heated tube.…”
Section: Introductionmentioning
confidence: 95%